PERAN KYAI DALAM MODERNISASI KURIKULUM DI PONDOK PESANTREN AL-FUTUHIYYAH ALI MASYKUR BUMIREJO MOJOTENGAH WONOSOB - Rochmanto, Achmad; Asy’ari, Abdurrahman; Mustofa Kamal, Muhammad Ali; Guefara, Rahmat Lutfi (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2024)
This article is the result of research on the role of kyai in curriculum modernization at the Al-Futuhiyyah Ali Masykur Islamic Boarding School, Bumirejo, Mojotengah, Wonosobo. This field research is the result of descriptive qualitative research by collecting data from questionnaires, observations, interviews and documentation to then be analyzed qualitatively through the stages of data reduction, data presentation, and verification/conclusion drawing. The findings conclude that the modernization of the curriculum of the Al-Futuhiyyah Ali Masykur Islamic Boarding School cannot be separated from the history of the founder of the institution. K.H. Masykur as the first caretaker and pioneer of the curriculum at the Islamic boarding school in 1971 provided the initial foundation of the curriculum. The second caretaker, K.H. Agus Munir fought in curriculum renewal by continuing the previously implemented curriculum and establishing a formal school, namely MTs Al-Futuhiyyah in 1983 and writing a work on nahwu science entitled "Nahwu in Indonesian" which is taught to students until now. The third caretaker, K.H. Ahmad Rofiq Masykur played a role in continuing the curriculum implemented by the previous caretaker, accompanied by updates in the Islamic boarding school curriculum by establishing SMP Alfa Ali Masykur in 2014 and updating the class levels by including the madrasah diniyah model that can be taken by students for six years, three years in ibtidaiyah and three years in tsanawiyah.